“Oh, the Red Viburnum in the Meadow”: Reflecting the Ukrainian National Mood - Petrovych Olha (Journal of Ethnology and Folkloristics)
The article investigates the Ukrainian folk song “Oh, the Red Viburnum in the Meadow”, recognised for its opening verse, and examines its historical, cultural, and social dimensions, alongside its various adaptations. By addressing questions of authorship and the folklore origins of the song, this study explores its transformations in response to prevailing socio-political contexts. The endurance of this tradition is traced from the Cossacks to the Sich Riflemen, the Ukrainian Insurgent Army and the modern Armed Forces’ soldiers of the Russo-Ukrainian War, as well as civilians. The research reveals the song’s dynamic interplay between historical tradition and contemporary relevance. The findings highlight the song’s power in building collective identity and expressing aspirations for independence, resistance and endurance.